Early Attachment Disruption, Inflammation, and Vulnerability for Depression in Rodent and Primate Models - Hennessy, Michael B.; Schiml, Patricia A.; Berberich, Katelyn; Beasley, Nicole L.; Deak, Terrence (Frontiers in Behavioral Neuroscience, 2019)
Early experiments in nonhuman primates established the relation between disruption of filial attachment and depressive-like outcomes. Subsequent studies in rats and mice have been instrumental in linking depressive-like outcomes to disturbances in maternal behavior. Another aspect of attachment disruption, absence of the attachment object per se, may be studied more effectively in a different laboratory rodent—the guinea pig. Here we discuss the rationale for using guinea pigs for this work. We then review guinea pig studies providing evidence for inflammatory mechanisms mediating both depressive-like behavior during separation as well as sensitization of stress responsiveness such as is thought to lead to increased vulnerability to depression at later ages. Finally, we discuss recent complementary work in adult monkeys that suggests cross-species generalizability of broad principles derived from the guinea pig experiments. Overall, the findings provide experimental support for human research implicating inflammatory mechanisms in the development of increased stress responsiveness and vulnerability to depression following attachment disruption and other forms of early-life stress. Specifically, the findings suggest inflammatory mechanisms may set in motion a cascade of underlying processes that mediate later increased stress responsiveness and, therefore, depression susceptibility.